1993
DOI: 10.1029/93gb00568
|View full text |Cite
|
Sign up to set email alerts
|

Global sources and sinks of OCS and CS2and their distributions

Abstract: This study investigates the distribution and magnitudes of the global sources and sinks of OCS and CS2. From an analysis of the correlations between measured emission rates and environmental parameters, the sources of OCS and CS2 are estimated to be 1.23 (0.83−1.71) Tg(OCS) yr−1 and 0.57 (0.34−0.82) Tg(CS2) yr−1, respectively. Our results indicate that 30% of the atmospheric OCS source is derived from the oxidation of CS2, while emissions from the ocean and other natural terrestrial sources contribute 28% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
268
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 247 publications
(275 citation statements)
references
References 69 publications
6
268
1
Order By: Relevance
“…The similarity in COS mixing ratios in most areas indicated that the prevailing monsoon in spring favors even distribution of the species with relatively long residual lifetime. The average COS mixing ratio in summer observed in this study was much lower than the background level (about 500 pptv), indicating strong COS uptake by vegetation (Chin and Davis, 1993;Xu, 2001;Watts, 2000;Campbell et al, 2008), whereas the extremely high levels of COS observed in winter indicated that additional COS emissions made remarkable contributions to atmospheric COS in Beijing.…”
Section: Seasonal Variationcontrasting
confidence: 54%
See 4 more Smart Citations
“…The similarity in COS mixing ratios in most areas indicated that the prevailing monsoon in spring favors even distribution of the species with relatively long residual lifetime. The average COS mixing ratio in summer observed in this study was much lower than the background level (about 500 pptv), indicating strong COS uptake by vegetation (Chin and Davis, 1993;Xu, 2001;Watts, 2000;Campbell et al, 2008), whereas the extremely high levels of COS observed in winter indicated that additional COS emissions made remarkable contributions to atmospheric COS in Beijing.…”
Section: Seasonal Variationcontrasting
confidence: 54%
“…e l s e v i e r . c o m / j o u r n a l -o f -e n v i r o n m e n t a l -s c i e n c e s atmospheric COS sinks (Chin and Davis, 1993;Watts, 2000;Kettle et al, 2002;Montzka et al, 2007), and can strongly reduce the COS mixing ratios at ground levels (Campbell et al, 2008).…”
Section: A V a I L A B L E O N L I N E A T W W W S C I E N C E D I mentioning
confidence: 99%
See 3 more Smart Citations